End-stage renal disease in children on maintenance dialysis in Benghazi, Libya - Barakat Ben Sauod, Ekram; Aklifa, Ahmed (Ibnosina Journal of Medicine and Biomedical Sciences, 2017)
Background: End-stage renal disease (ESRD) is a major cause of morbidity and mortality worldwide. Understanding the risk factors of ESRD can help identify preventive strategies and is critical for planning interventions to minimize the disease morbidity and mortality. Objectives: The aim is to identify the demographic and clinical characteristics and risk factors that contribute to ESRD 2005–2016. Settings: The dialysis unit of Benghazi Pediatric Hospital, Benghazi, Libya. Patients and Methods: This is a descriptive case series of all children with ESRD on maintenance dialysis (hemodialysis or peritoneal dialysis) between January 2006 and June 2016. Data were collected from patients' charts and the statistics department of the hospital. Demographic information, the age of onset, duration, and type of dialysis, likely etiology (if documented), complications and comorbidities were all documented and outcome including the cause of death. Results: The mean age of onset of ESRD was 8.5 years; nearly 41% of patients started dialysis at 6–10 years. The majority of patients (72%) resided locally. Male to female ratio was 1.5:1. Consanguinity of parents and family history of renal disease were reported by 12% and 16% of patients, respectively. More than half of patients (51.3%) had had no complications from dialysis. The most common known cause of ESRD was glomerulopathy (18.4%); including glomerulonephritis and nephrotic syndrome. Congenital and hereditary disorders involved 17.1% of cases. These were obstructive uropathy in 9.2% of the patients. The cause was not known in a large proportion (52.6%). Nearly 80% of the patients were alive during the study. Encephlophay (10.5%) and sepsis (6.5%) are the most common causes of death. Conclusions: The clinical profiles, causes, and outcome of ESRD in a specialized center in Benghazi were documented. The study is limited by the high proportion of unknown etiology. Full documentation of underlying etiology is a good clinical practice that should produce better epidemiological studies.
Keywords: End-stage renal disease; hemodialysis dialysis; peritoneal dialysis; risk factors